PROSES MANUFAKTUR MESIN PRES LEMBARAN (SHEET PRESS MACHINE) - Dimas Alviyanto (2021)
Plastic is the most used and produced material compared to other materials, of course it increases the amount of plastic waste that exists. Therefore, the utilization of plastic waste should be maximized so that plastic waste can be reused. In this paper, the topic is about making sheet press machine tools. The purpose of this paper is to produce a sheet press machine that can make 90x50cm plastic waste sheets to replace fiber material. The sheet press machine uses a hydraulic jack to lift the bottom mold plate to press plastic waste. The jack is placed under the bottom heating plate bracket which is connected to the frame. This machine was created with an estimated price of Rp.3.375.149.